1982
DOI: 10.1246/bcsj.55.1971
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Molecular Structure of cis-Diaqua[(7S, 14S)-5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclo-tetradecane]nickel(II) Chloride

Abstract: A six-coordinate diaqua nickel(II) complex with the title macrocyclic ligand, [Ni(H2O)2(S,S-L)]Cl2, has been synthesized and its structure has been determined by the X-ray analysis. Coordination geometry about the Ni is of cis-NiO2N4 type with the macrocyclic ligand folded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Cis V is the only configuration found, within 25 kJ/mol of the lowest conformation, in a conformational search of bismul, cis -diaqua( C - rac- 5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane)nickel(II). The next lowest configuration, trans III, is more than 40 kJ/mol higher in energy.…”
Section: Resultsmentioning
confidence: 99%
“…Cis V is the only configuration found, within 25 kJ/mol of the lowest conformation, in a conformational search of bismul, cis -diaqua( C - rac- 5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane)nickel(II). The next lowest configuration, trans III, is more than 40 kJ/mol higher in energy.…”
Section: Resultsmentioning
confidence: 99%
“…The chloride counter ions interact with the water ligands through O-H···Cl hydrogen bonds. Similarly configured nickel cyclam complexes were reported by Ito et al (1981Ito et al ( , 1982. A recent crystal structure search in the CCDC database has shown that only 4% of cyclam complexes without nitrogen functionalization, utilizing halogen containing counter ions and monodentate ligands for the final two coordination sites, adopt a cis V configuration (Allen, 2002).…”
Section: D-hámentioning
confidence: 62%
“…For metal complex formation, see: Sadler et al (2007); Voelcker et al (2008). For nickel cyclam complex crystal structures with a cis-V configuration, see: Sadler et al (2007); Ito et al (1981Ito et al ( , 1982; Allen (2002). For details of peptide racemization, see: Liardon & Ledermann (1986).…”
Section: Related Literaturementioning
confidence: 99%